Is tenofovir/emtricitabine teratogenic?. (June 2013) - Jibril, Murtala; Egunsola, Oluwaseun
The Truvada ® (tenofovir/emtricitabine) and nevirapine combination is increasingly being prescribed for prevention of mother-to-child HIV transmission. There is presently no documented evidence of teratogenicity of either tenofovir/emtricitabine or nevirapine. We report two cases of spina bifida in infants of mothers on this drug combination.